An economic analysis of trade-secret protection in buyer-seller relationships - Stefan Bechtold; Felix Höffler (Max Planck Institute for Research on Collective Goods, 2007)
The economic analysis of trade-secret protection has traditionally focused on the interests of companies to conceal information from competitors in order to gain competitive advantage through trade-secret law. This has neglected cases in which the interest is not in concealing information from competi- tors, but from trading partners. We investigate the social e ciency eects of trade-secret protection in such cases. Many results from economic theory state that asymmetric information (and therefore also its legal protection) is socially undesirable since it leads to ine cient trade. At the same time, protecting private information might create incentives for socially desirable investments. We model this trade-o in a simple buyer-seller model and nd that, indeed, trade-secret protection has ambiguous welfare eects. However, a simple, informationally undemanding rule, conditioning the applicability of legal protection on a minimum investment by the informed party to conceal the information, helps to apply trade-secret protection only when it increases welfare. This rationalizes important features of current legal practice, but sug- gests that the eort to conceal rather than the eort to reveal the information should play a role when deciding whether or not trade secret protection should be granted.
Keywords: K2; D82; 330; disclosure of information; hold-up problems; trade secrets; Geschäftsgeheimnis; Lieferanten-Kunden-Beziehung; Informationsverhalten; Wohlfahrtseffekt; Theorie